Improved protocol for the vitrification and warming of rat zygotes by optimizing the warming solution and oocyte donor age - Naomi Nakagata; Satohiro Nakao; Nobuyuki Mikoda; Katsuma Yamaga; Yoshiko Nakagawa; Tetsushi Sakuma; Takashi Yamamoto; Toru Takeo (PLoS ONE, 2025)
Zygotes are used to create genetically modified animals by electroporation using the CRISPR-Cas9 system. Such zygotes in rats are obtained from superovulated female rats after mating. Recently, we reported that in vivo-fertilized zygotes had higher cryotolerance and developmental ability than in vitro-fertilized zygotes in Sprague Dawley (SD) and Fischer 344 rats. To apply the in vitro-fertilized zygotes in creating genetically modified rats, we need to address their low cryotolerance and developmental ability. Hence, we evaluated the effects of warming solutions containing different sucrose concentrations (0–0.3 M) and the oocyte donor’s age (3–7-week-old SD rats) on the viability of vitrified-warmed zygotes after in vitro fertilization and on developmental ability by embryo transfer in SD rats. A warming solution containing 0.1 M sucrose enhanced the survival rate of vitrified-warmed zygotes and their rate of development to two-cell embryos. Additionally, zygotes derived from 6- and 7-week-old female rats had higher cryotolerance and developmental ability than those from 3-week-old ones. Next, vitrified-warmed rat zygotes produced using the optimized protocol underwent genome editing by electroporation with Cas9 ribonucleoprotein and gRNA introduced to disrupt the Tyr gene. We then found that 86.5% of the pups derived from zygotes demonstrated mutation of the targeted gene. Therefore, the improved protocol for vitrifying and warming rat zygotes is useful for preserving and producing genetically modified rats.